The Brilliance of the Zebrafish Model: Perception on Behavior and Alzheimer’s Disease - Shenoy, Avinash; Banerjee, Meheli; Upadhya, Archana; Bagwe-Parab, Siddhi; Kaur, Ginpreet (Frontiers in behavioral neuroscience, 2022)
Alzheimer’s disease (AD) has become increasingly prevalent in the elderly population across the world. It’s pathophysiological markers such as overproduction along with the accumulation of amyloid beta (Aβ) plaques and neurofibrillary tangles (NFT) are posing a serious challenge to novel drug development processes. A model which simulates the human neurodegenerative mechanism will be beneficial for rapid screening of potential drug candidates. Due to the comparable neurological network with humans, zebrafish has emerged as a promising AD model. This model has been thoroughly validated through research in aspects of neuronal pathways analogous to the human brain. The cholinergic, glutamatergic, and GABAergic pathways, which play a role in the manifested behavior of the zebrafish, are well defined. There are several behavioral models in both adult zebrafish and larvae to establish various aspects of cognitive impairment including spatial memory, associative memory, anxiety, and other such features that are manifested in AD. The zebrafish model eliminates the shortcomings of previously recognized mammalian models, in terms of expense, extensive assessment durations, and the complexity of imaging the brain to test the efficacy of therapeutic interventions. This review highlights the various models that analyze the changes in the normal behavioral patterns of the zebrafish when exposed to AD inducing agents. The mechanistic pathway adopted by drugs and novel therapeutic strategies can be explored via these behavioral models and their efficacy to slow the progression of AD can be evaluated.